2004
DOI: 10.1111/j.1445-1433.2004.03263.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of endoleak following endoluminal abdominal aortic aneurysm repair

Abstract: Initial observation is a reasonable management option in most cases of type II endoleak, because some will spontaneously resolve during follow up. Those associated with increase in aneurysm size should undergo interventional treatment. Conservative management of type I endoleaks may be undertaken in extreme isolated cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…CT allows the detection of graft failure, as suggested by a growing aneurysmal sac, device migration, or endoleak. Although type I and III endoleaks require immediate reintervention [8,9], type II endoleaks can often be managed conservatively because a significant proportion of them spontaneously resolve [7,8,19]. As such, when a type II endoleak is detected on CT follow-up, it is logical to ask whether the CT features have any prognostic value.…”
Section: Discussionmentioning
confidence: 99%
“…CT allows the detection of graft failure, as suggested by a growing aneurysmal sac, device migration, or endoleak. Although type I and III endoleaks require immediate reintervention [8,9], type II endoleaks can often be managed conservatively because a significant proportion of them spontaneously resolve [7,8,19]. As such, when a type II endoleak is detected on CT follow-up, it is logical to ask whether the CT features have any prognostic value.…”
Section: Discussionmentioning
confidence: 99%
“…12,16 However, some researchers found that a number of slight type I endoleaks were self-limited or sealed spontaneously, which could be treated only when the aneurysm sac enlarged. 7,8,17 The best management of immediate type I and type III endoleaks detected during an EVAR procedure remains unclear. Moreover, the significance of these endoleaks on long-term outcomes is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…During our follow-up, 24 patients were observed to have spontaneously resolved endoleaks, and this was in accordance with previous reports. 7,8,18,19 For these patients, surgical intervention as well as its costs are redundant. Thus, an objective evaluation method to predict the outcomes of such endoleaks during the EVAR procedure could help operators decide on whether to reintervene immediately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 This success has resulted in a significant increase in the number of EVARs performed in the United States. 2 Although EVAR represents a major advance in the management of aortic aneurysm disease, it comes with a price: the increased risk of postoperative (usually late) complications, 3 which mandates vigilant postoperative surveillance protocols using computed tomographic (CT), intraaortic sac pressure measurement or duplex ultrasound technology (DU).…”
Section: Introductionmentioning
confidence: 99%